The Impact of Familial Expectations on Career Choices and Identity Formation in Highly Educated Women - Akbari, Roya; Hoseinzadeh, Aliasghar (Psychology of Woman Journal, 2025)
Objective: This study aims to explore the impact of familial expectations on career choices and identity formation among highly educated women in Tehran.Methods and Materials: The study employed a qualitative design, using semi-structured interviews with 24 highly educated women from Tehran. Participants were selected through purposive sampling to capture diverse perspectives. Data collection continued until theoretical saturation was achieved, ensuring comprehensive thematic coverage. The interviews were transcribed and analyzed using thematic analysis, facilitated by NVivo software. Four primary themes emerged: familial expectations, career choices, identity formation, and coping mechanisms.Findings: The results revealed that familial expectations significantly influenced participants’ career choices, often delaying entry into the workforce and leading to compromises in professional aspirations. Participants described internal conflicts between societal roles and personal ambitions, which shaped their identity formation. Coping mechanisms included emotional strategies, resistance to traditional norms, and pragmatic adaptations. These findings highlighted the pervasive influence of cultural norms on women’s autonomy and professional development.Conclusion: Familial expectations create significant barriers to career advancement and identity formation for highly educated women in Tehran. These dynamics underscore the need for supportive organizational policies, cultural shifts toward gender equality, and interventions that empower women to navigate these challenges effectively. The study contributes to the literature on gender roles, work-family conflict, and women’s professional empowerment, offering actionable insights for policymakers, educators, and organizations.